Influence of Teachers’ Pedagogical Beliefs on Technology Integration in Language Education within Global Learning Contexts - Imelda Kusumastuty; Dina Destari; Noura Rizqyannisa Hidayat (International Forum of Researchers and Lecturers, 2024)
This study explores the influence of teachers' pedagogical beliefs on the integration of technology in language education. Teachers' beliefs significantly impact their technology adoption and how it is utilized in the classroom, shaping the learning experiences of students. The research uses a mixed-methods approach, combining quantitative surveys and qualitative interviews with classroom observations to examine the relationship between teachers’ beliefs and their use of technology in language education settings. The findings reveal that teachers with constructivist beliefs, which emphasize active, student-centered learning, are more likely to integrate technology in ways that support engagement, collaboration, and critical thinking. In contrast, teachers with traditional, teacher-centered beliefs are more likely to use technology primarily for content delivery and repetition, limiting its potential to foster interactive and student-driven learning environments. The study also highlights the gap between teachers' positive beliefs about technology and their actual practices, which are often hindered by external barriers such as lack of training, resources, and institutional support. The research suggests that professional development programs should address both pedagogical beliefs and technological competencies to facilitate successful technology integration. Furthermore, the study calls for future research to explore how specific pedagogical models, like constructivism, can be further aligned with technology integration to improve learning outcomes. The research also emphasizes the need for longitudinal studies to understand the evolution of teachers' beliefs and their impact on technology use in language education.